Exploring the role of programme managers on employees performance at the Department of Social Development at Mopani District, Limpopo Province - Shilaluke, Given (My University, 2021)
The current split between the Department of Health and Social Development had made a great impact on employees’ performance. The transition has resulted on previously shared resources to being divided. The division of resources made a great impact on employees’ performance at the Department of Social Development. The adjustment to the transition has been a difficult task towards employees in the department of Social Development. Programme managers whose employees are reporting to, had to come up with management strategies to enhance performance. The research problem is a problem because nothing is known about what the senior management is doing in order to enhance performance at Mopani District. It seems that no study has been conducted to determine the challenges experienced by programme managers on employees’ performance. The major objective of the study to determine the current programmes which are used by the Department to enhance performance in the area of study and to suggest strategies that can be used by the senior management to enhance performance at Mopani District. The nature of this study is qualitative. It is an exploratory study. Data was collected be through semi-structured interviews. The sampling of this study is non-probability sample. In non-probability sampling, the researcher selected purposive sampling. Data was analyzed in a narrative from. Findings show that the programme managers are faced with several challenges in the organization. Programme managers do not have the necessary resources. Programmes offered by the programme managers are not enhancing employees’ performance due to inadequate equipments provided by the department. Current strategies used by the programme managers are no longer relevant, hence poor employees’ performance. The senior managers should be encouraged to develop relevant training programmes, minimize challenges and provide necessary resources that could be employed by the programme managers to enhance the performance of employees at the department of Social Development in Mopani district.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2021
Keywords: Programme managers; Employees Performance; Social development; Employees -- Rating of -- South Africa -- Limpopo; Goal setting in personnel management -- South Africa -- Limpopo; Employees -- Training of -- South Africa -- Limpopo